Low-impurity biomass hard carbon as well as preparation method and application thereof
Through the impurity removal process of large fungi absorbs impurities, the problem of difficulty in removing impurities in hard carbon materials in biomass is solved, its sodium storage performance and circulation stability are improved, and a green and environmentally friendly low-cost preparation is achieved.
Patent Information
- Application Number
- CN202411573538.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
AI Technical Summary
The existing biomass hard carbon materials are difficult to remove impurities during the high-temperature carbonization process, resulting in poor sodium storage performance and circulation stability. The traditional acid-base washing method is costly and has serious environmental pollution.
Large fungi are used to absorb impurities in biomass raw materials, and remove inorganic salts and metal elements through the mushroom removal process to avoid acid and base treatment and maintain microporous structure.
It effectively reduces the impurity content in hard carbon of biomass, improves its sodium storage performance and cycle stability, and has environmentally friendly processes and low cost, with industrial application prospects.
Smart Images

Figure CN119400860A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for sodium ion batteries, in particular to low-impurity biomass hard carbon and a preparation method and application thereof. Background Art
[0002] Hard carbon (charcoal) refers to carbon materials that are difficult to graphitize and maintain a disordered structure at high calcination temperatures. Biomass hard carbon prepared from biomass has the advantages of low cost, simple preparation process, and renewability, and can be made into negative electrode materials for sodium ion batteries. However, biomass raw materials usually contain high levels of impurities, such as inorganic salts, metal ions, etc. These impurities are difficult to remove during the high-temperature carbonization process, resulting in a high impurity content in biomass hard carbon, which limits its sodium storage performance.
[0003] At present, acid and alkali washing is the mainstream process for removing impurities from hard carbon. However, this method not only has high production costs and is prone to environmental pollution, but also the acid and alkali treatment process is prone to corroding the microporous structure of hard carbon, resulting in an increase in specific surface area and a decrease in sodium storage performance. Therefore, a new green, pollution-free and low-cost method for preparing and removing impurities from biomass hard carbon is urgently needed. Summary of the invention
[0004] To this end, the technical problem to be solved by the present invention is to provide a low-impurity biomass hard carbon and its preparation method and application. The method can effectively remove impurities such as inorganic salts and metal elements in the biomass raw materials used to prepare the biomass hard carbon, while maintaining the microporous structure of the biomass hard carbon material, so as to improve its sodium storage performance and cycle stability in the negative electrode material of the sodium ion battery.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A low-impurity biomass hard carbon is obtained by carbonizing biomass raw material powder after removing impurities; when removing impurities from the biomass raw material powder, large fungi are used to absorb impurity elements in the biomass raw material powder to reduce the content of impurity elements in the biomass raw material powder.
[0007] The above-mentioned low-impurity biomass hard carbon, the content of impurity element lithium in the low-impurity biomass hard carbon is less than or equal to 25 mg / kg, the content of calcium is less than or equal to 3000 mg / kg, the content of sodium is less than or equal to 250 mg / kg, the content of phosphorus is less than or equal to 200 mg / kg, and the content of potassium is less than or equal to 850 mg / kg.
[0008] The influence of impurities, or impurity elements, on the quality and performance of biomass hard carbon mainly lies in reducing the capacity of hard carbon, causing electrolyte side reactions, and precipitation of impurity metal dendrites leading to micro short circuits inside the battery, etc. Therefore, impurity removal steps are usually required when preparing biomass hard carbon.
[0009] The raw materials for making biomass hard carbon usually come from plants. For plants, the metal elements in their bodies mainly include potassium, calcium, magnesium, copper, iron, zinc and manganese, which are all impurities that need to be removed during the preparation of biomass hard carbon. In addition, plants generally contain a large amount of phosphorus, and the phosphorus element usually exists in the form of acid radicals, which is difficult to be converted into gas and removed during the high-temperature carbonization process. These impurity elements are easily absorbed nutrients for the growth of large fungi. Therefore, large fungi can effectively remove impurity elements in biomass raw materials that are not conducive to the preparation of biomass hard carbon.
[0010] "Macrofungi" refers to fungi that can form fleshy or gelatinous fruiting bodies or sclerotia. Macrofungi can effectively absorb and utilize inorganic salts in biomass raw materials, that is, impurity elements in the form of inorganic salts in biomass raw materials are absorbed into the fruiting bodies of macrofungi. In addition, macrofungi can decompose cellulose and lignin in biomass to produce CO 2 , H 2 O, small molecule sugars and organic acids and other metabolites. Among them, the low-carbon organic matter such as small molecule sugars produced will melt during the carbonization process and fill the large pores, making it easier for the impurity-removed biomass raw material powder to form a rich closed microporous structure during the carbonization process, further improving the sodium storage capacity of the prepared biomass hard carbon.
[0011] A method for preparing low-impurity biomass hard carbon comprises the following steps:
[0012] S1. Mixing biomass raw material powder with strains of macrofungi and cultivating until the macrofungi grow fruiting bodies;
[0013] S2, removing the fruiting bodies of large fungi growing on the biomass raw material powder, baking the remaining matter and then sieving it to obtain the impurity-free biomass raw material powder;
[0014] S3, carbonizing the impurity-removed biomass raw material powder to obtain the above-mentioned low-impurity biomass hard carbon.
[0015] In the actual production process, when the content of impurity elements in the biomass raw material powder is too high, the time for cultivating and spawning the biomass raw material powder can be appropriately extended, that is, multiple spawning and multiple harvesting of fruiting bodies can be carried out to achieve the purpose of deep impurity removal. However, during multiple spawning, large fungi will also consume a large amount of carbon elements in the biomass raw material powder, and extend the production cycle of biomass hard carbon, resulting in a decrease in the output of biomass hard carbon.
[0016] In the above-mentioned preparation method, in step S1, the preparation method of the biomass raw material powder used is: the biomass raw material is crushed to a particle size less than or equal to 2 mm. When the particle size of the biomass raw material powder is too large, it is easy to cause insufficient impurity removal. When the particle size is too small, the energy consumed in the carbonization process increases, and it is easy to burn out, resulting in a decrease in the yield of biomass hard carbon.
[0017] In the above-mentioned preparation method, in step S1, the biomass raw material powder is washed and then mixed with the strains of large fungi: the washing liquid used for washing the biomass raw material powder is sodium hydroxide solution or ammonia water; the pH of the washing liquid is 7-8, the temperature during washing is 60-80°C, and the washing time is 0.5-2h. Using heated sodium hydroxide or ammonia water to wash the crushed biomass raw material can not only remove impurities such as sand contained in the biomass raw material, but also kill part of the miscellaneous bacteria in the biomass raw material, providing suitable conditions for the subsequent cultivation of large fungi. And when using ammonia water for washing, the nitrogen in the ammonia water can also be absorbed and utilized by large fungi. When the washing temperature is too low or the time is too short, it is difficult to kill the miscellaneous bacteria, and the effect of washing away impurities is poor. When the washing temperature is too high or the time is too long, the energy consumption is high, which is not conducive to energy saving.
[0018] In the above-mentioned preparation method, in step S1, the biomass raw material used to prepare the biomass raw material powder is any one of straw, bagasse, eucalyptus and bamboo, or a mixture of two or more thereof.
[0019] In the above-mentioned preparation method, in step S1, the water content of the biomass raw material powder used is 40wt% to 60wt%. The water content of the biomass raw material powder will mainly affect the hyphae growth of large fungi in the early stage of cultivation.
[0020] In the above-mentioned preparation method, in step S1, the large fungus is any one of oyster mushroom, shiitake mushroom and tea tree mushroom; when mixed, the mass ratio of biomass raw material powder to the strain of large fungus is 100: (5-20). Oyster mushroom, shiitake mushroom and tea tree mushroom have low requirements for the environment and nutrition, and do not need to add additional substances such as nutrient solution that are conducive to the growth of mushrooms, and can grow better on biomass raw material powder. When the mass ratio of biomass raw material powder to the strain of large fungus is within this range, the large fungus can smoothly grow fruiting bodies within 30 to 60 days and complete the removal of impurities from the biomass raw material powder. When the amount of strain added is too little, the time required to grow fruiting bodies will be extended, and when the amount added is too much, the cost will be too high.
[0021] In the above preparation method, in step S2, the temperature of the residue baking is 60-80°C, and the baking time is 10-24 hours; when the residue is sieved, it is sieved through a 5-mesh sieve; the purpose of baking is to dehydrate and shrink the hyphae of the large fungi, so as to separate the biomass raw material powder and the hyphae. If the baking time is too long, the mycelium will become too fragile and easily break into powder, making it difficult to separate the hyphae from the biomass raw material powder.
[0022] In step S3, when the impurity-removed biomass raw material powder is carbonized, low-temperature carbonization and high-temperature carbonization are sequentially performed under a nitrogen protective atmosphere; the temperature during low-temperature carbonization is 400-600°C, and the low-temperature carbonization time is 6-8 hours; the temperature during high-temperature carbonization is 1000-1300°C, and the high-temperature carbonization time is 4-6 hours. Since the impurity-removed biomass raw material powder is relatively fluffy and has more volatiles, carbonization by low-temperature carbonization and then high-temperature carbonization is beneficial to improving the biomass hard carbon yield and saving energy consumption.
[0023] The application of low-impurity biomass hard carbon is: using the low-impurity biomass hard carbon to prepare negative electrode materials for sodium ion batteries.
[0024] The technical solution of the present invention achieves the following beneficial technical effects:
[0025] 1. The present invention absorbs inorganic salts in biomass raw materials through mushrooms, effectively removes impurity elements, and decomposes cellulose and lignin in the process to generate low-carbon organic matter. These low-carbon organic matter promotes the formation of more closed microporous structures in biomass hard carbon during the carbonization process; and the step of removing impurity elements in the present invention is carried out before carbonization, and no acid washing or alkali washing is required after carbonization, which effectively prevents the closed microporous structure from being destroyed by acid or alkali, so that the obtained biomass hard carbon is not only loose and porous, but also has a smaller specific surface area. This feature significantly improves the sodium storage capacity of biomass hard carbon, so that the sodium ion battery negative plate made of biomass hard carbon exhibits excellent sodium storage performance. In addition, the reduction of impurity elements effectively prevents the occurrence of electrolyte side reactions and micro-short circuits inside the battery, thereby improving the first coulomb efficiency and cycle stability of the sodium ion battery.
[0026] 2. The method provided in the present invention uses edible mushrooms as a tool for absorbing impurities in biomass raw materials. The entire impurity removal process does not require the use of corrosive chemicals, reducing pollution to the environment. At the same time, the growth process of mushrooms is simple and economical, and can be sold as a by-product, improving the economic benefits of the entire hard carbon material production chain. This green and environmentally friendly preparation process significantly reduces production costs and has prospects for industrial application.
[0027] 3. Compared with the traditional acid-base washing and complex heat treatment process, the biomass impurity removal method adopted in the present invention has simplified steps, more operational process, can remove impurity elements in biomass under low energy consumption conditions, and can effectively avoid the damage of chemical treatment to the microporous structure of biomass hard carbon. Experiments show that the first coulombic efficiency, first charge specific capacity, first discharge specific capacity and coulombic efficiency after 50 charge and discharge cycles of low-impurity biomass hard carbon prepared by the method of the present invention are comparable to those of biomass hard carbon removed by acid washing first and then alkali washing, and the first coulombic efficiency is even better. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 XRD pattern of the biomass hard carbon prepared in Example 1 of the present invention;
[0029] Figure 2 The charge and discharge curve of the electrode made of biomass hard carbon prepared in Example 1 of the present invention;
[0030] Figure 3 Cycling curve of the electrode made of biomass hard carbon prepared in Example 1 of the present invention;
[0031] Figure 4 XRD spectrum of the biomass hard carbon prepared in Comparative Example 1 of the present invention;
[0032] Figure 5 The charge and discharge curve of the electrode made of biomass hard carbon prepared in Comparative Example 1 of the present invention;
[0033] Figure 6 Cycling curve of the electrode made of biomass hard carbon prepared in Comparative Example 1 of the present invention;
[0034] Figure 7 XRD spectrum of the biomass hard carbon prepared in Comparative Example 2 of the present invention;
[0035] Figure 8 The charge and discharge curve of the electrode made of biomass hard carbon prepared in Comparative Example 2 of the present invention;
[0036] Fig. 9 Cycling curve of the electrode made of biomass hard carbon prepared in Comparative Example 2 of the present invention;
[0037] Fig.10 XRD spectrum of the biomass hard carbon prepared in Comparative Example 3 of the present invention;
[0038] Fig.11 The charge and discharge curve of the electrode made of biomass hard carbon prepared in Comparative Example 3 of the present invention;
[0039] Fig.12 Cycling curve of the electrode made of biomass hard carbon prepared in Comparative Example 3 of the present invention;
[0040] Fig.13 XRD spectrum of the biomass hard carbon prepared in Comparative Example 4 of the present invention;
[0041] Fig.14 The charge and discharge curve of the electrode made of biomass hard carbon prepared in Comparative Example 4 of the present invention;
[0042] Fig.15 Cycling curve of the electrode made of biomass hard carbon prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0043] Example 1
[0044] In this embodiment, a low-impurity corn stalk hard carbon was prepared, and the prepared low-impurity corn stalk hard carbon was further made into a negative electrode of a sodium ion battery.
[0045] The preparation method of low-impurity corn stalk hard carbon in this embodiment is:
[0046] S1. Crush 2kg corn stalks to a particle size of less than 2mm to obtain biomass raw material powder. Then transfer the biomass raw material powder to a sodium hydroxide aqueous solution with a pH of 8, stir and wash at 80°C for 1h, and filter press until the moisture content is 40wt%. The biomass raw material powder after filter press is mixed with the Pleurotus ostreatus strain in a mass ratio of 100:10, and mycelium culture and fruiting body culture are carried out in sequence under suitable conditions for Pleurotus ostreatus culture until fruiting bodies (i.e., mushrooms) grow. The culture time is a total of 40 days. In some other embodiments, the culture time can also be flexibly adjusted according to the growth of the fruiting body and the content of impurity elements in the biomass raw material, but it should be within the range of 30 to 60 days in general. When the culture time is too long, the production cycle of biomass hard carbon is too long, and the carbon element in the biomass raw material will also be consumed in large quantities by large fungi, resulting in a decrease in yield.
[0047] S2. Harvest the oyster mushrooms (fruiting bodies) grown on the biomass raw material powder, that is, remove the oyster mushrooms grown on the biomass raw material powder, bake the remaining material at 80° C. for 12 h, and then pass it through a 5-mesh sieve, and the material under the sieve is the impurity-free biomass raw material powder.
[0048] S3, carbonizing the impurity-free biomass raw material powder. The specific method is to first perform low-temperature carbonization on the impurity-free biomass raw material powder at 500°C for 6 hours, and then perform high-temperature carbonization at 1300°C for 4 hours. After the high-temperature carbonization, low-impurity corn stalk hard carbon is obtained.
[0049] The biomass hard carbon prepared in this example is used as the negative electrode of the sodium ion battery and its sodium storage performance is tested. The preparation method of the battery negative electrode is:
[0050] (1) Low-impurity corn straw hard carbon, conductive agent Super P and sodium alginate were mixed and ground evenly in a mass ratio of 8:1:1, and dispersed in ultrapure water to prepare electrode slurry.
[0051] (2) The obtained electrode slurry is evenly coated on copper foil, and vacuum dried at 80°C for 12 hours to obtain a negative electrode sheet. Then, a sheet press is used to press and shape the coated sheet (i.e., the copper foil coated with the electrode slurry), and then cut to obtain a hard carbon negative electrode sheet for a sodium ion battery.
[0052] The prepared materials for making sodium-ion batteries were assembled in a vacuum glove box in the order of negative electrode shell-hard carbon negative electrode-glass fiber membrane-electrolyte-sodium sheet-gasket-spring sheet-positive electrode shell, and then put into a button cell packaging machine for sheeting. The electrolyte used was 1M NaPF 6 / DIG (diethylene glycol dimethyl ether) solution. The compacted battery was left horizontally for 24 hours for testing.
[0053] Sodium storage performance test: LAND blue battery charge and discharge tester was used to test the sodium storage performance at 30mA g -1 The charge and discharge performance test was carried out in the current density range of 0.01 to 1.5 V, and the test temperature was kept constant at 25°C.
[0054] The electrode charge and discharge curves obtained by the test are as follows: Figure 2 As shown in the figure, 1st represents the first charge and discharge curve, 2nd represents the second charge and discharge curve, and 3rd represents the third charge and discharge curve. The first cycle discharge capacity is 258.6mAh / g, and the charge capacity is 238.6mAh / g, showing a high first coulomb efficiency of 92.3%. Its cycle performance is as follows Figure 3 As shown, after 50 cycles, the charge capacity is 238.6 mAh / g, with no capacity decay, showing excellent stability.
[0055] The XRD spectrum of the low-impurity corn straw hard carbon prepared in this embodiment is as follows: Figure 1 shown.
[0056] The comparison of impurity element contents of low-impurity corn stalk hard carbon prepared in Example 1, corn stalk hard carbon without mushroom impurity removal (preparation method see Comparative Example 1 for details) and acid-base hard carbon (preparation method see Comparative Example 4 for details) are shown in Table 1. The corn stalk hard carbon prepared in Comparative Example 1 was not impurity-removed. Based on the content of each element in Comparative Example 1, the impurity removal rates of the mushroom impurity removal in Example 1 and the impurity removal by acid washing followed by alkali washing in Comparative Example 4 were calculated.
[0057] Table 1 Impurity element content in hard carbon
[0058]
[0059]
[0060] From the results in Table 1, it can be seen that the impurity removal of the oyster mushroom in Example 1 has a good impurity removal effect, especially for the elements of zinc, lithium, calcium, sodium, phosphorus and potassium, the impurity removal of the oyster mushroom can play a better impurity removal effect than the impurity removal method of first acid washing and then alkali washing. For silicon, iron, titanium and aluminum elements, the impurity removal effects of the oyster mushroom impurity removal method and the impurity removal method of first acid washing and then alkali washing are also relatively close.
[0061] Example 2
[0062] In this embodiment, a low-impurity bagasse hard carbon was prepared, and the prepared low-impurity bagasse hard carbon was further made into a negative electrode of a sodium ion battery.
[0063] The preparation method of low-impurity bagasse hard carbon in this embodiment is:
[0064] S1. Grind 2kg of sugarcane bagasse to a particle size of less than 2mm to obtain biomass raw material powder. Transfer the biomass raw material powder to a sodium hydroxide aqueous solution with a pH of 8, stir and wash at 60°C for 1h, and then filter press until the moisture content is 50wt%. Mix the biomass raw material powder after filter pressing with the mushroom strain in a mass ratio of 100:20, and perform mycelium culture and fruiting body culture in sequence under suitable conditions for mushroom culture until fruiting bodies (i.e., mushrooms) grow. The culture time is a total of 40 days.
[0065] S2. Harvesting the mushrooms (fruiting bodies) grown on the biomass raw material powder, that is, removing the mushrooms grown on the biomass raw material powder, baking the remaining material at 60° C. for 10 h, and then passing through a 5-mesh sieve, and the material under the sieve is the impurity-free biomass raw material powder.
[0066] S3, carbonizing the impurity-free biomass raw material powder. The specific method is to firstly perform low-temperature carbonization on the impurity-free biomass raw material powder at 500°C for 6 hours, and then perform high-temperature carbonization at 1300°C for 4 hours. After the high-temperature carbonization, low-impurity sugarcane bagasse hard carbon is obtained.
[0067] The method for preparing the low-impurity bagasse hard carbon in this embodiment into a hard carbon negative electrode sheet for a sodium ion battery is the same as that in Example 1. The method for testing the electrode sodium storage performance of the prepared hard carbon negative electrode sheet for a sodium ion battery is the same as that in Example 1, and the test results are shown in Table 2.
[0068] Example 3
[0069] In this embodiment, a low-impurity eucalyptus hard carbon is prepared, and the prepared low-impurity eucalyptus hard carbon is further made into a negative electrode of a sodium ion battery.
[0070] The preparation method of low-impurity eucalyptus hard carbon in this embodiment is:
[0071] S1. Crush 2kg of eucalyptus wood to a particle size of less than 2mm to obtain biomass raw material powder. Then transfer the biomass raw material powder to a sodium hydroxide aqueous solution with a pH of 8, stir and wash at 80°C for 1h, and then filter press until the moisture content is 60wt%. The biomass raw material powder after filter press is mixed with the tea tree mushroom strain in a mass ratio of 100:20, and hyphae culture and fruiting body culture are carried out in sequence under suitable conditions for tea tree mushroom culture until fruiting bodies (i.e., mushrooms) grow. The total culture time is 40 days.
[0072] S2. Harvest the Agrocybe aegerita (fruiting body) grown on the biomass raw material powder, i.e. remove the Agrocybe aegerita grown on the biomass raw material powder, bake the remaining material at 80° C. for 10 h, and then pass it through a 5-mesh sieve, and the material under the sieve is the impurity-free biomass raw material powder.
[0073] S3, carbonizing the impurity-free biomass raw material powder. The specific method is to firstly perform low-temperature carbonization on the impurity-free biomass raw material powder at 500°C for 6 hours, and then perform high-temperature carbonization at 1300°C for 6 hours. After the high-temperature carbonization, low-impurity eucalyptus hard carbon is obtained.
[0074] The method for preparing the low-impurity eucalyptus hard carbon in this embodiment into a hard carbon negative electrode sheet for a sodium ion battery is the same as that in Example 1. The method for testing the electrode sodium storage performance of the prepared hard carbon negative electrode sheet for a sodium ion battery is the same as that in Example 1, and the test results are shown in Table 2.
[0075] Comparative Example 1
[0076] In this comparative example, corn straw hard carbon was prepared, and the prepared corn straw hard carbon was further made into the negative electrode of the sodium ion battery.
[0077] The preparation method of corn straw hard carbon in this comparative example is:
[0078] 2 kg of corn stalks were crushed to a particle size of <2 mm, then transferred to deionized water, stirred and washed at 80°C for 1 h, filter pressed and dried; then carbonized at 500°C for 6 h, and then high-temperature carbonized at 1300°C for 4 h to prepare corn stalk hard carbon.
[0079] The main difference between the corn straw hard carbon in this comparative example and that in Example 1 in terms of preparation method is that in this comparative example, the biomass raw material powder has not been subjected to oyster mushroom impurity removal.
[0080] The method for preparing the hard carbon anode sheet of sodium ion battery from the corn stalk hard carbon in this comparative example is the same as that in Example 1. The method for testing the electrode sodium storage performance of the prepared hard carbon anode sheet of sodium ion battery is the same as that in Example 1, and the test results are shown in Table 2.
[0081] Figure 4 The XRD pattern of the corn stalk hard carbon prepared in Comparative Example 1 shows an obvious impurity peak at 31.2°, indicating that it is difficult to remove impurities in the corn stalk raw material by simple washing. Figure 5 As shown in FIG. 1 , the first cycle discharge specific capacity is 233.0 mAh / g, the charge specific capacity is 165.0 mAh / g, and the first coulombic efficiency is 70.8%. The cycle performance of the sodium ion battery in this comparative example is shown in FIG. Figure 6 As shown, the charge capacity after 50 cycles is 200.6 mAh / g. Compared with Example 1, Comparative Example 1 exhibits lower first coulombic efficiency and cycle stability.
[0082] Comparative Example 2
[0083] In this comparative example, corn straw hard carbon was prepared, and the prepared corn straw hard carbon was further made into the negative electrode of the sodium ion battery.
[0084] The preparation method of corn straw hard carbon in this comparative example is:
[0085] 2 kg corn stalks were crushed to a particle size of <2 mm, then transferred to deionized water, stirred and washed at 80°C for 1 hour, filtered and dried; then carbonized at 500°C for 6 hours, transferred to 1M HCl solution for immersion for 24 hours, filtered and washed until neutral; finally, carbonized at 1300°C for 4 hours to prepare corn stalk hard carbon;
[0086] The main difference between the corn stalk hard carbon in this comparative example and that in Example 1 in terms of the preparation method is that in this comparative example, the biomass raw material powder after low-temperature carbonization is removed by acid washing, while the oyster mushroom is not removed.
[0087] The method for preparing the hard carbon anode sheet of sodium ion battery from the corn stalk hard carbon in this comparative example is the same as that in Example 1. The method for testing the electrode sodium storage performance of the prepared hard carbon anode sheet of sodium ion battery is the same as that in Example 1, and the test results are shown in Table 2.
[0088] Figure 7 The XRD diagram of the corn straw hard carbon prepared in Comparative Example 2 shows that the lower impurity peaks still have impurities remaining after acid washing. Figure 8 As shown in FIG. 1 , the first cycle discharge capacity is 291.4 mAh / g, the charge capacity is 234.2 mAh / g, and the first coulombic efficiency is 80.4%. The cycle performance of the sodium ion battery in Comparative Example 2 is shown in FIG. Fig. 9 As shown, the charge capacity after 50 cycles is 238.5 mAh / g. Compared with Example 1, Comparative Example 2 exhibits worse first coulombic efficiency and cycle stability.
[0089] Comparative Example 3
[0090] In this comparative example, corn straw hard carbon was prepared, and the prepared corn straw hard carbon was further made into the negative electrode of the sodium ion battery.
[0091] The preparation method of corn straw hard carbon in this comparative example is:
[0092] 2 kg of corn stalks were crushed to a particle size of <2 mm, then transferred to deionized water, stirred and washed at 80°C for 1 h, filtered and dried; then carbonized at 500°C for 6 h, transferred to 1M NaOH solution and soaked for 24 h, filtered and washed until neutral; finally, carbonized at 1300°C for 4 h to prepare corn stalk hard carbon.
[0093] The main difference between the corn stalk hard carbon in this comparative example and that in Example 1 in terms of the preparation method is that in this comparative example, the alkaline washing method is used to remove impurities from the biomass raw material powder after low-temperature carbonization, while the oyster mushroom impurity removal is not performed.
[0094] The method for preparing the hard carbon anode sheet of sodium ion battery from the corn stalk hard carbon in this comparative example is the same as that in Example 1. The method for testing the electrode sodium storage performance of the prepared hard carbon anode sheet of sodium ion battery is the same as that in Example 1, and the test results are shown in Table 2.
[0095] Fig.10 The XRD diagram of the corn stalk hard carbon prepared in Comparative Example 3 shows that impurity peaks can still be observed in the figure, indicating that impurities still remain after alkali washing. Fig.11 As shown in FIG. 3 , the first cycle discharge capacity is 271.4 mAh / g, the charge capacity is 222.4 mAh / g, and the first coulombic efficiency is 81.9%. The cycle performance of the sodium ion battery in Comparative Example 3 is shown in FIG. Fig.12 As shown, the charge capacity after 50 cycles is 243.4 mAh / g. Compared with Example 1, Comparative Example 3 exhibits worse first coulombic efficiency and cycle stability.
[0096] Comparative Example 4
[0097] In this comparative example, corn straw hard carbon (acidic and alkaline hard carbon) was prepared, and the prepared corn straw hard carbon was further made into the negative electrode of the sodium ion battery.
[0098] The preparation method of corn stalk hard carbon (acid-base hard carbon) in this comparative example is:
[0099] 2 kg corn stalks were crushed to a particle size of <2 mm, then transferred to deionized water, stirred and washed at 80°C for 1 hour, filtered and dried; then carbonized at 500°C for 6 hours, transferred to 1M HCl solution and soaked for 24 hours, then transferred to 1M NaOH solution and soaked for 24 hours, filtered and washed until neutral; finally, carbonized at 1300°C for 4 hours to prepare corn stalk hard carbon (acidic and alkaline hard carbon);
[0100] The main difference in the preparation method of the corn stalk hard carbon (acidic and alkaline hard carbon) in this comparative example and that in Example 1 is that in this comparative example, the method of acid washing followed by alkali washing is used to remove impurities from the biomass raw material powder after low-temperature carbonization, while the impurities of the oyster mushroom are not removed.
[0101] The method for preparing the hard carbon anode sheet of sodium ion battery from the corn stalk hard carbon (acidic and alkaline hard carbon) in this comparative example is the same as that in Example 1. The method for testing the electrode sodium storage performance of the prepared hard carbon anode sheet of sodium ion battery is the same as that in Example 1, and the test results are shown in Table 2.
[0102] Fig.13 The XRD diagram of the corn stalk hard carbon (acid-base hard carbon) prepared in Comparative Example 4 shows that after acid-base washing, the impurity peak is significantly weakened, indicating that very few impurities remain. Fig.14 As shown in FIG. 4 , the first cycle discharge capacity is 287.7 mAh / g, the charge capacity is 255.1 mAh / g, and the first coulombic efficiency is 88.7%. The cycle performance of the sodium ion battery in Comparative Example 4 is shown in FIG. Fig.15 As shown, the charge capacity after 50 cycles is 281.1 mAh / g. Compared with Example 1, Comparative Example 4 shows a worse first coulombic efficiency.
[0103] Table 2 Comparison of electrode sodium storage performance.
[0104]
[0105]
[0106] The better the sodium storage performance of the electrode, the better it is. It mainly refers to the ability of the electrode material to store and release sodium ions during the charge and discharge process. It is usually measured by specific capacity (unit: mAh / g), which indicates the amount of charge that can be stored per gram of material in one charge and discharge cycle. The higher the specific capacity, the stronger the sodium storage capacity of the material.
[0107] Comparing the measurement results of the first coulombic efficiency, it can be seen that the first coulombic efficiency in the above three embodiments (92.3% to 94.6%) is significantly higher than that in the comparative example (70.8% to 88.7%). Among them, the first coulombic efficiency of Example 3 is the highest, reaching 94.6%, while the comparative example 1 is the lowest, only 70.8%. A high first coulombic efficiency means that less electricity is lost during the first charging process, which indicates that the hard carbon material after large fungus impurities removal has better electrochemical stability and active site utilization in the initial cycle.
[0108] Comparing the measurement results of the first charge specific capacity, it can be seen that the charge specific capacity (238.6 mAh / g to 252.1 mAh / g) in the above three embodiments is generally higher than that in the comparative example (165.0 mAh / g to 255.1 mAh / g), especially the charge specific capacity of comparative example 1 is significantly lower, only 165.0 mAh / g. This shows that the biomass raw materials that have not been treated with fungi retain more impurities during the carbonization process, affecting the electrochemical reaction efficiency of the material. The first charge specific capacity efficiency of comparative example 3 and comparative example 4 can be inferred that large fungus impurity removal can obtain a similar impurity removal effect as acid washing followed by alkali washing.
[0109] Comparing the measurement results of the first discharge specific capacity, it can be seen that the discharge specific capacity (258.6 mAh / g to 266.5 mAh / g) in the above three embodiments is also higher than that in the comparative example (233.0 mAh / g to 287.7 mAh / g). Although the discharge specific capacity of comparative example 4 is higher (287.7 mAh / g), its acid-base washing method is complicated, and the first coulomb efficiency (88.7%) is still lower than that of examples 1, 2 and 3.
[0110] Comparing the charge capacity measurement results after 50 cycles, it can be seen that the electrodes in the above three embodiments maintain a charge capacity of 238.6 mAh / g to 252.1 mAh / g after 50 cycles, with almost no attenuation, showing excellent cycle stability. In contrast, the charge capacity in the comparative examples has decreased, especially in comparative example 1, where the charge capacity has dropped to 200.6 mAh / g, showing a large capacity attenuation.
[0111] In the above three embodiments, inorganic impurities and metal elements in the biomass raw materials are effectively removed by the method of large-scale fungus impurity removal. These impurities usually affect the conductivity and sodium storage capacity of the carbon material during the carbonization process. However, Comparative Example 1 has not been impurity-removed, resulting in poor sodium storage performance, especially the first coulomb efficiency and cycle stability. Comparative Examples 2 and 3 use chemical methods such as acid washing or alkali washing, but their effects are still not as good as large-scale fungus impurity removal, and complex chemical treatments may have an adverse effect on the microstructure of the material. Overall, when the low-impurity biomass hard carbon obtained after large-scale fungus impurity removal is made into the negative electrode of a sodium ion battery, its electrode sodium storage performance is closer to that of the biomass hard carbon obtained by first acid washing and then alkali washing.
[0112] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A low-impurity biomass hard carbon, characterized in that: The low-impurity biomass hard carbon is obtained by carbonizing biomass raw material powder after removing impurities; when removing impurities from the biomass raw material powder, large fungi are used to absorb the impurity elements in the biomass raw material powder to reduce the content of the impurity elements in the biomass raw material powder.
2. The low-impurity biomass hard carbon according to claim 1, characterized in that: The impurity element lithium content in the low-impurity biomass hard carbon is less than or equal to 25 mg / kg, the calcium content is less than or equal to 3000 mg / kg, the sodium content is less than or equal to 250 mg / kg, the phosphorus content is less than or equal to 200 mg / kg, and the potassium content is less than or equal to 850 mg / kg.
3. A method for preparing low-impurity biomass hard carbon, characterized in that: The following steps are involved: S1. Mixing biomass raw material powder with strains of macrofungi and cultivating until the macrofungi grow fruiting bodies; S2, removing the fruiting bodies of large fungi growing on the biomass raw material powder, baking the remaining matter and then sieving it to obtain the impurity-free biomass raw material powder; S3, carbonizing the impurity-removed biomass raw material powder to obtain the low-impurity biomass hard carbon as claimed in claim 1.
4. The preparation method according to claim 3, characterized in that: In step S1, the biomass raw material powder is prepared by grinding the biomass raw material into particles less than or equal to 2 mm.
5. The preparation method according to claim 3, characterized in that: In step S1, the biomass raw material powder is washed and then mixed with the strains of large fungi: the washing liquid used for washing the biomass raw material powder is sodium hydroxide solution or ammonia water; the pH of the washing liquid is 7-8, the washing temperature is 60-80°C, and the washing time is 0.5-2h.
6. The preparation method according to claim 3, characterized in that: In step S1, the biomass raw material used to prepare the biomass raw material powder is any one of straw, bagasse, eucalyptus and bamboo, or a mixture of two or more thereof.
7. The preparation method according to claim 3, characterized in that: In step S1, the water content of the biomass raw material powder used is 40wt% to 60wt%.
8. The preparation method according to claim 3, characterized in that: In step S1, the macrofungus is any one of Pleurotus ostreatus, Lentinus edodes and Agrocybe edulis; when mixed, the mass ratio of the biomass raw material powder to the macrofungus strain is 100:(5-20).
9. The preparation method according to claim 3, characterized in that: In step S2, the temperature of the residue is 60-80°C, and the baking time is 10-24 hours; when the residue is sieved, it is sieved through a 5-mesh sieve; In step S3, when the impurity-removed biomass raw material powder is carbonized, low-temperature carbonization and high-temperature carbonization are performed in sequence under a nitrogen protective atmosphere; the temperature during low-temperature carbonization is 400-600°C, and the low-temperature carbonization time is 6-8 hours; the temperature during high-temperature carbonization is 1000-1300°C, and the high-temperature carbonization time is 4-6 hours.
10. Application of low-impurity biomass hard carbon, characterized in that: The application is: using the low-impurity biomass hard carbon as claimed in claim 1 to prepare negative electrode materials for sodium ion batteries.
Citation Information
Cited By
Bagasse hard carbon negative electrode material low-cost iron removal process based on bacterial biological method
CN120922848A
A low-cost iron removal process for sugarcane bagasse hard carbon negative electrode material based on bacterial biological method
CN120922848B